The Influence of ATLAS Utilization, Auditor Competence, and Time Pressure on Audit Quality at Public Accounting Firms in Bali Province - Andari, Anak Agung Putu Rista; Widhiyani, Ni Luh Sari; Sujana, I Ketut (CV. Proaksara Global Transeduka, 2025)
The reliability of financial statements depends heavily on audit quality, which evaluates both the auditing procedures and their outcomes as performed by auditors. This research aimed to gather empirical evidence regarding how Atlas usage, auditor expertise, and time constraints influence audit quality within public accounting firms operating in Bali Province. Using purposive sampling methods, the study collected 46 observations from Bali-based public accounting firms that utilize Atlas software. The researchers employed multiple linear regression analysis to examine the data. The findings shed light that Atlas implementation positively and significantly impacts audit quality, auditor expertise also demonstrates a significant positive relationship with audit quality, and time constraints show a significant influence on audit quality outcomes. These findings align with attribution theory principles, as they demonstrate how individual behavioral factors influence auditor performance, which subsequently affects the overall quality of audit work.